DESKRIPSI PARTISIPASI AKTIF, DAN KEMAMPUAN KOMUNIKASI MATEMATIS MAHASISWA PADA MATA KULIAH GEOMETRI ANALITIK BIDANG MELALUI PENERAPAN LESSON STUDY - Wanda Nugroho Yanuarto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
The purpose of this study was to describe the active participation, independent learning, and mathematical communication skills of students in the field of analytic geometry courses through the implementation of lesson study. The study consisted of four cycles, each cycle shall be composed of three stages: plan, do, see. The subjects were students of first semester 2014 in class A of mathematics education, The University of Muhammadiyah Purwokerto. The data of this research were through observation sheets, video recordings, portfolios, and questionnaires. The data were analyzed through data reduction, data presentation, and conclusion. The results showed that the students' learning motivation can be increased with learning-based lesson study. Keywords: active participation, independent learning, mathematical communication, lesson study